Identification of troponin I and actin, alpha cardiac muscle 1 as potential biomarkers for hearts of electrically stimulated chickens - Amid, Azura; Abu Samah, Norshahida; Yusof, Faridah (BioMed Central Ltd, 2012)
Methods: In this study, proteomics methods have been used to study the effects of different currents and voltages used to stun chickens. Protein profiles of chicken hearts were constructed to detect differences in protein expression and modification. The different voltages studied were 10 V, 40 V and 70 V, while the currents examined were 0.25 A, 0.5 A, and 0.75 A. The profiles obtained from these stunning conditions were compared to the nonstunned (0 A, 0 V) sample. Results: Proteomics analyses using 2D Platinum ImageMaster 6.0 and Matrix-assisted laser desorption/ionization with time-of-flight mass spectrometry (MALDI-TOF) identified troponin I and alpha cardiac muscle actin 1 in the electrically stimulated heart samples. The overexpression of the proteins was further confirmed at the transcriptional level by Real Time PCR. Conclusion: The results from MALDI-TOF and Real Time PCR agreed; therefore, this method for identifying biomarkers of electrically stimulated chicken hearts provides a novel approach for differentiation the hearts of increased electrically stimulated chickens from those of non-stunned chickens.